Teknologi dan komunikasi dakwah nabi : studi media tradisional di era kenabian dan implementasi strategi dakwah rasulullah di era digital - maghfirah, putri (Maliki Interdisciplinary Journal, 2026)
This study examines the forms and characteristics of traditional media used by Prophet Muhammad SAW in delivering Islamic da'wah, as well as their relevance to modern digital da'wah strategies. Using a qualitative library research approach, the study explains how the Prophet utilized oral communication, letters, and poetry as effective da'wah media. Core communication principles such as qaulan sadidan, qaulan layyinan, and qaulan balighan guided his ethical communication style. These values remain relevant in the digital era and can be implemented through social media, podcasts, and other digital platforms while maintaining ethical and responsible Islamic communication. In the digital age, the values ​​of the Prophet Muhammad's missionary communication remain relevant and need to be implemented through the wise use of information technology. Educational institutions and students need further development of research on the Prophet's missionary communication, and the Muslim community is expected to utilize digital media positively and selectively.